2005
DOI: 10.1186/1745-9974-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stroke location on the laryngeal cough reflex and pneumonia risk

Abstract: Background: The purpose of this study was to evaluate the risk of developing pneumonia in acute stroke patients comparing the early anatomical stroke location and laryngeal cough reflex (LCR) testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…A similar study investigating VC and RC in stroke patients found that 10% of patients had a weak or absent CR, whereas 20% of patients had an abnormal VC (Addington, Stephens, & Gilliland, 1999). Addington et al (2005) also suggest that cerebral infarcts can result in transient, or permanent, 'brainstem shock' which can result in impaired cough reflex. Ward et al (2010) investigated the difference between RC and VC in patients following ischaemic hemispheric stroke and in healthy controls.…”
Section: Differences Between Reflexive and Voluntary Coughingmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study investigating VC and RC in stroke patients found that 10% of patients had a weak or absent CR, whereas 20% of patients had an abnormal VC (Addington, Stephens, & Gilliland, 1999). Addington et al (2005) also suggest that cerebral infarcts can result in transient, or permanent, 'brainstem shock' which can result in impaired cough reflex. Ward et al (2010) investigated the difference between RC and VC in patients following ischaemic hemispheric stroke and in healthy controls.…”
Section: Differences Between Reflexive and Voluntary Coughingmentioning
confidence: 99%
“…It has been suggested that the amygdalo-hypothalamo-reticular pathway and supratentorial connections act to modulate brainstem control of the cough reflex, as disruption of these regions following cerebral infarcts can result in dystussia (Addington, Stephens, Widdicombe, & Rekab, 2005). It has also been hypothesized that voluntary suppression of coughing is mediated by the pyramidal tracts and that any impairment to these tracts could result in a lower suppressed cough reflex threshold (Smith & Wiles, 1998).…”
Section: Neurological Control Of Coughmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with lower evoked cough sensitivity and slower swallowing responses were more likely to develop pneumonia. Addington and colleagues found that if a patient had a brainstem or cerebral stroke and an abnormal laryngeal cough reflex (LCR), they had a significantly higher risk of pneumonia [17]. In their study of 818 patients admitted with stroke, they found that 90% of patients had a normal LCR to tartaric acid and only 3% of this group developed pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Other stimuli such as pressure to mechanoreceptors in the hypopharynx above the trachea, innervated by afferents form the glossopharyngeal nerve were found to be much less effective for eliciting a cough (Hegland, Pitts, Bolser, et al, 2011). Some have proposed that the capsaicin test might be predictive of risk of aspiration in patients with swallowing disorders post stroke (Addington, Stephens and Gilliland, 1999), however the sensitivity and specificity were not good (Addington, Stephens, Widdicombe, et al, 2005). …”
Section: Systems Driving the Laryngeal Musculaturementioning
confidence: 99%